2018
DOI: 10.1007/s12011-018-1326-x
|View full text |Cite
|
Sign up to set email alerts
|

Trace Elements in Saliva as Markers of Type 2 Diabetes Mellitus

Abstract: To analyze Mg, Ca, and Zn levels in saliva, comparing patients with type 2 diabetes mellitus and a control group of healthy subjects. This transversal, observational, clinical study included a total sample of 147 patients, 74 with type 2 diabetes mellitus and a control group of 73 healthy subjects. Socio-demographic, anthropometric, diabetological, and metabolic variables were registered. Trace elements in non-stimulated basal saliva were measured using inductively coupled plasma mass spectrometry (ICP-MS): Mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 33 publications
1
8
0
1
Order By: Relevance
“…The involved metabolic processes include the following: de novo fatty acid biosynthesis; saturated fatty acid beta-oxidation; butanoate metabolism; glycolysis and gluconeogenesis; tricarboxylic acid cycle; urea cycle; metabolism of proline, glutamate, aspartate and asparagine; valine, leucine and isoleucine (BCAA) degradation; aminosugar metabolism; purine metabolism; and glycerophospholipid metabolism. Overall, this information, along with that of other recent progress regarding the study of salivary simple analytes [4], trace elements [59], major adipocytokines [60,61], and specific microRNAs [62], reinforces the idea that saliva will soon represent a useful tool for deepening pathomechanismistic aspects, noninvasive diagnosis and monitoring of pediatric and adult individuals with obesity. The early and non-invasive detection of incipient MetS/fatty liver in childhood through salivary metabolomics as described here, therefore, appears as a promising helpful tool to prevent further health hepato-metabolic and cardiovascular complications in adulthood, and ultimately serves to minimize their related global socioeconomic burden.…”
Section: Discussionsupporting
confidence: 62%
“…The involved metabolic processes include the following: de novo fatty acid biosynthesis; saturated fatty acid beta-oxidation; butanoate metabolism; glycolysis and gluconeogenesis; tricarboxylic acid cycle; urea cycle; metabolism of proline, glutamate, aspartate and asparagine; valine, leucine and isoleucine (BCAA) degradation; aminosugar metabolism; purine metabolism; and glycerophospholipid metabolism. Overall, this information, along with that of other recent progress regarding the study of salivary simple analytes [4], trace elements [59], major adipocytokines [60,61], and specific microRNAs [62], reinforces the idea that saliva will soon represent a useful tool for deepening pathomechanismistic aspects, noninvasive diagnosis and monitoring of pediatric and adult individuals with obesity. The early and non-invasive detection of incipient MetS/fatty liver in childhood through salivary metabolomics as described here, therefore, appears as a promising helpful tool to prevent further health hepato-metabolic and cardiovascular complications in adulthood, and ultimately serves to minimize their related global socioeconomic burden.…”
Section: Discussionsupporting
confidence: 62%
“…The saliva samples were centrifuged at 3500 rpm for 10 min. An aliquot of 500 µL was subsampled from the supernatant of each sample and, then, diluted at 5 mL using a 1% v/v sub-boiled nitric acid solution [ 29 , 30 ]. A Thermo Finnigan Element 2 sector field inductively coupled plasma mass spectrometry (SF-ICP-MS) system, equipped with a glass concentric nebulizer and a Twinnabar (cyclonic) spray chamber, was used for the measurements of the following elements: Li, Na, Mg, Mn, Fe, Cu, Zn, Ca, K, and Rb.…”
Section: Methodsmentioning
confidence: 99%
“…At present, studies on salivary secretion in patients with T2DM have mainly focused on the comparison of salivary indicators between diabetic and non-diabetic individuals, due to the limitation of clinical research. Several studies have shown that diabetic patients and healthy individuals had significant differences in the salivary parameters, including salivary glucose, sAA, s-IgA, sialic acid, total salivary protein and ion concentration (3)(4)(5)(6)(7), and diabetic patients exhibited pathological changes in the autonomic nervous system (8). Research on salivary secretion in diabetic animal model has been focused on pathological observation and associated mechanisms of salivary glands, due to the technological difficulty of salivary acquisition.…”
Section: Introductionmentioning
confidence: 99%